Pengaruh Sistem Lantai dan Tingkat Kepadatan Kandang Terhadap Performance Produksi Ayam Arab Jantan Periode Grower - Ajeng Megawati Putri; Muharlien Muharlien; Ita Wahju Nursita (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2017)
The purpose of this study was to determine the effect of litter system and interaction of both different level of cage density grower arab chicken. The material used were 48 arabic chicken at grower period which the age 2 months and the average weight 701.7±94.37 g and the value SD 13.45%. The method used in this study was experimented with completely randomized design (CRD) factorial patterns. First factor was litter system dan second factor was the level of cage density. Data were analyzed by analysis of variance (ANOVA) , if there was different followed by duncan multiple range test. The results showed that litter system of cage was not showed any significant effect (P>0.05) on feed consumption, weight growth and feed conversion. The level of cage density was gave significant different (P<0.01) on feed consumption, weight growth and feed conversion. Interaction between litter system and different level of cage density were not gave significant effect (P>0.05). The conclusion of this study there was not interaction between factor litter system and the level of cage density.